2021
DOI: 10.1016/j.heliyon.2021.e08023
|View full text |Cite
|
Sign up to set email alerts
|

Dirac equation and thermodynamic properties with the Modified Kratzer potential

Abstract: In this work, we present the analytical solutions of Dirac equation for modified Kratzer potential in the pseudospin and spin symmetry limits using the formula method. The energies of the pseudospin and spin symmetry limit are obtained analytically and numerically. The numerical values are compared with those obtained in literature. Furthermore, we study the thermodynamic properties of some diatomic molecules within the nonrelativistic spin symmetry limits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 36 publications
0
3
0
1
Order By: Relevance
“…( 77) is the nonrelativistic energy eigenvalue 𝐸 𝑚𝑘 𝑛𝑟 for the modified Kratzer potential consistent with the energy in Refs. [5,83,84] under NRQM symmetries, while the second part is due to the effect of deformation of the space-space for the modified Kratzer potential.…”
Section: The Improved Mie-type Potential Problems In Nreqm Symmetriesmentioning
confidence: 99%
See 1 more Smart Citation
“…( 77) is the nonrelativistic energy eigenvalue 𝐸 𝑚𝑘 𝑛𝑟 for the modified Kratzer potential consistent with the energy in Refs. [5,83,84] under NRQM symmetries, while the second part is due to the effect of deformation of the space-space for the modified Kratzer potential.…”
Section: The Improved Mie-type Potential Problems In Nreqm Symmetriesmentioning
confidence: 99%
“…Recently, Onyenegecha et al used the formula technique to present the analytic solutions of DE for the modified Kratzer potential under the p-spin and spin symmetries and found the energies analytically and numerically. They also investigated the thermodynamic properties of the 𝑋 1 Σ + 𝑔 state of Cl 2 and N 2 diatomic molecules in the nonrelativistic spin symmetry limit [5]. Under the pspin symmetry, Aydogdu and Sever [6] found an explicit solution of DE for a pseudoharmonic potential in the presence of a linear tensor potential and demonstrated that tensor interactions erase all degeneracies between the members of pseudospin doublets.…”
Section: Introductionmentioning
confidence: 99%
“…Schrodinger dengan potensial telah banyak dikaji di antaranya melibatkan potensial Coulomb (Karomah et al, 2021), Osilator Harmonik (Rusmini et al, 2022), Kratzer (Onyenegecha et al, 2021). Selain itu, potensial yang dikaji juga dapat berupa gabungan dari beberpa jenis potensial seperti Hulthen-Hellmann (Akpan et al, 2021), Potensial Quadratik Yukawa dan Eckart (Antia et al, 2020), Wood-Saxon (Suparmi et al, 2021), Hulthen-Non Sentral Posch Teller (Sunarmi et al, 2013) dan lain-lain.…”
Section: Pendahuluanunclassified
“…Studying thermodynamic properties of systems involves the determination of the partition function. In addition to entropy, specific heat capacity, mean free energy, and others, a partition function allows us to obtain different thermodynamic properties [24,25].…”
Section: Introductionmentioning
confidence: 99%